Analisis Efektivitas Metode Turun Lapangan dalam Menentukan Penerima Bansos terhadap Distribusi Bansos - Rizti, Muthia; Kusmilawaty; Fahdhila, Tri Inda (SAFE-Network, 2025)
This study aims to determine the effectiveness of the field method in determining recipients of social assistance, through the Integrated Referral Service System at the Tanjungbalai City Social Service. Based on the results of the study, it was found that the implementation of the SLRT program in Tanjungbalai City has been running quite well. This type of research is descriptive research with a qualitative approach. The specific results obtained are, the SLRT program in Tanjungbalai City shows progress in achieving target accuracy and timeliness, although there are still some errors in collecting recipients. Then, although the data used in this program is quite complete, there are some discrepancies between the existing data and conditions in the field, especially related to the changing economic status of recipients. Then, the SLRT program in Tanjungbalai City has successfully adapted well to field conditions, especially with geographical and accessibility limitations. Then, socialization regarding the SLRT program has been carried out quite well to the sub-district and village levels, although there are still some people who do not fully understand how this program works and its objectives. Overall, this study shows that the SLRT program in Tanjungbalai City can be said to be effective, but several aspects such as targeting accuracy, data updates, and socialization need to be improved to achieve more optimal results in poverty alleviation.